Identification of SikCDPK family genes to low-temperature by RNA-seq approaches and functional analysis of SikCDPK1 in Saussurea involucrata (Kar. & Kir.) - Shi, Guangzhen; Liu, Yuling; Tian, Xiaohan; Guo, Jiaxiu; Zhu, Xinxia (Frontiers in Plant Science, 2024)
Calcium-Dependent Protein Kinases (CDPKs) are a class of serine/threonine protein kinases encoded by several gene families that play key roles in biotic and abiotic stresses response and plant growth and development. However, snow lotus (Saussurea involucrata kar L.)CDPKs has rarely been reported. In this study, 20 CDPK genes in snow lotus were identified based on transcriptome data and classified into four groups (I-IV) based on their structural features and phylogenetic analyses. Among them, the transcript levels of SikCDPK1 were significantly induced by low temperature and multiple hormone treatments, and SikCDPK1 gene was found to have different expression in snow lotus seeds, leaves, stems and roots. The full-length promoter activity of SikCDPK1 gene was higher than that of the 5' end deletion fragment, and the promoter fragment containing the low temperature inducing element had increased activation after low temperature treatment. The promoter activity of SikCDPK1 gene was mainly expressed in roots and rosette leaves. In addition, overexpressing plants of SikCDPK1 were more tolerant compared to the wild type after being subjected to low temperature stress. Physiological analyses indicated that SikCDPK1 improved plant tolerance to low temperature stress by maintaining cell membrane stability and reducing the accumulation of reactive oxygen species (ROS). These findings provided insights into CDPK gene families in snow lotus and broaden our understanding of the biological role of SikCDPK1 and the mechanism of low temperature stress tolerance in snow lotus.